CHANGES OF PERIFERAL BLOOD PARAMETERS AND IMMUNOLOGICAL STATUS OF PATIENTS WITH CHRONICAL HERPETIC INFECTION WITHOUT ANT WITH SYMPTOMATIC FOCAL EPILEPSY - S. V. Krijzhanovskaya; N. L. Kamzalakova; N. A. Shnayder; Yu. S. Panina (Эпилепсия и пароксизмальные состояния)
Abstract: Purpose of the study is аssessment of changes in the peripheral blood parameters and immune status of patients with chronic herpes infection without and with symptomatic (parainfection) focal epilepsy. Materials and Metods. the study included 128 adults. Group 1 – control (40 pers.; median age – 31 ye.o., 2 group – patients with chronic herpes virus infection without symptomatic focal epilepsy (43 pers.; median age – 35 ye.o.). 3 group – patients with chronic herpes virus infection complicated by symptomatic focal epilepsy (45 pers.; median age – 32 ye.o.). Volume of research: history of the disease, epidemiological history, neurological examination, video-EEG monitoring, MRI, MR-spectroscopy, immune status, serology, immunologist consultation. Results. The analysis of immune status of the patients with chronic herpes infection has shown significant differences between the studied parameters compared with the control group, as well as comparisons between groups. We were shown lymphocytosis, imbalance of immunoregulatory subpopulations, reducing the immunoregulatory index. Serological studies in patients 2 and 3 groups of 100% of the cases were shown specific G class antibodies to HSV, a high titer of antibodies found in patients 2 groups accession symptomatic focal epilepsy, p <0.01. Also, the study was shown a reduce of Ig A level in groups 2 and 3 compared with the control. Statistically significantly more frequently in patients two groups met chronic recurrent herpesvirus mixed infection. Conclusions. The patients with chronic herpes infection with symptomatic focal epilepsy revealed more serious violations in the humoral and cellular immunity, adversely affecting the formation of specific antiviral response. This testifies to the prolonged course of infection , which is a predictor of high risk of forming refractory symptomatic (parainfection ) focal epilepsy.